Unraveling industry, firm and host-region effects on export behaviors of international new ventures and established exporters - Ine Paeleman; Shaker A. Zahra; Jonas W. B. Lang (National Bank of Belgium, 2021)
While an extensive strategy literature seeks to explain differences in firm performance, little is known about how much firm, industry and host-regions matter in explaining heterogeneity in export behaviors. The international entrepreneurship literature has highlighted that firm-, industry- and hostregion- level factors shape export behaviors, yet more research is needed about their relative contribution. We decompose the variance of export behaviors of 4,982 Belgian SMEs during 2006-2014. Results indicate that firm effects account for the largest part in the variation of export behaviors, followed by industry and host-region effects. However, host-region effects matter more for INVs whereas firm effects matter more for established exporters. There are no substantial differences in industry effects among either sample of firms. Our study contributes to the literatures on variance decomposition and international entrepreneurship.
Keywords: 330; new ventures; host-region effects; firm effects; export; variance decomposition